Arctic Shipping and Risks : Emergency Categories and Response Capacities - Marchenko, Nataliya A.; Andreassen, Natalia; Borch, Odd Jarl; Kuznetsova, Svetlana Yu.; Ingimundarson, Valur; Jakobsen, Uffe (TransNav, the International Journal on Marine Navigation and Safety of Sea Transportation, 2018)
publishedVersion